(untitled) (Journal of Economic Research & Business Administration, 2024)
The study’s goal was to determine the environmental and climate change issues that the BRICS nations are now confronting, the steps that have been taken to address these challenges, and the outcomes of Agenda 2030 and other initiatives that have been done. Secondary data collection, qualitative analysis, and exploratory analysis were all done as part of this study. Secondary data, such as government reports and records, published research papers, websites, and other pertinent materials, are the basis for content analysis. Strict measures such as planting trees, prohibiting the chopping down of trees and clearing jungles, prohibiting the demolition of mountains, creating space for playgrounds, addressing issues with air and water pollution, and addressing noise pollution are necessary to ensure the security of the future, are required to take. As with the growth and development due to urbanization, pollution of various kinds has reached great heights and coping with these challenges has become difficult for every living being, that is, both plants and animal kingdom. A greener and cleaner tomorrow will welcome the future generation, if we take the initiative from now onwards by taking it as our responsibility towards the future generation. There is tremendous urbanization. The nations’ expansion and progress are occurring at the expense of the wellbeing of their wildlife and flora, including people. It has become a threat to human civilization and the existing vegetations and animals. If serious action against the global threat of environmental pollution and Climate Change is not taken, the repercussion will be severe. It is the sole duty of the current generation to give the future generation a healthy tomorrow. Because of the obstacles presented by environmental and climate change, it is now imperative that each individual bear the responsibility of overcoming these issues. Key words: Challenges, Environmental, BRICS countries, climate change, pollution, urbanization, future generation.